2005
DOI: 10.1111/j.1745-6584.2005.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Glacial Sediment Causing Regional‐Scale Elevated Arsenic in Drinking Water

Abstract: In the upper Midwest, USA, elevated arsenic concentrations in public drinking water systems are associated with the lateral extent of northwest provenance late Wisconsin-aged drift. Twelve percent of public water systems located within the footprint of this drift (212 of 1764) exceed 10 microg/L arsenic, which is the U.S. EPA's drinking water standard. Outside of the footprint, only 2.4% of public water systems (52 of 2182) exceed 10 microg/L arsenic. Both glacial drift aquifers and shallow bedrock aquifers ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 32 publications
3
55
0
Order By: Relevance
“…For As in glacial aquifers, this principle has been demonstrated through a statistical comparison of As concentrations in 1000s of wells on a regional-scale with screened intervals with varying proximity to an aquitard. Wells that were screened near the aquitard were more likely to have elevated well-water As concentrations than wells with screens farther from the aquitard (Erickson and Barnes, 2005a). These findings generated the first tractable explanation for the geographic distribution of elevated As in wells completed in confined glacial aquifers: the aquifer-aquitard contact zone is a hot-spot for As mobilization from the solidphase to the aqueous-phase (Erickson and Barnes, 2005b).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…For As in glacial aquifers, this principle has been demonstrated through a statistical comparison of As concentrations in 1000s of wells on a regional-scale with screened intervals with varying proximity to an aquitard. Wells that were screened near the aquitard were more likely to have elevated well-water As concentrations than wells with screens farther from the aquitard (Erickson and Barnes, 2005a). These findings generated the first tractable explanation for the geographic distribution of elevated As in wells completed in confined glacial aquifers: the aquifer-aquitard contact zone is a hot-spot for As mobilization from the solidphase to the aqueous-phase (Erickson and Barnes, 2005b).…”
Section: Introductionmentioning
confidence: 85%
“…The crustal average is about 5.1 mg kg À1 (Rudnick and Gao, 2003). The highest As concentration found in any of the sediments measured for this study is 12.1 mg kg À1 , the lowest concentration was 2.6 mg kg À1 , the average concentration was 6.6 mg kg À1 and the median concentration was 6.8 mg kg elevated-As wells is strongly heterogeneous with respect to geography and well depth and previous research based on well-water chemistry and well-construction records suggested that the aquitard/aquifer interface was the likely source of As from solids to waters (Erickson and Barnes, 2005a). Wells with screened intervals close to an aquitard are more likely to have elevated well-water As concentrations than wells with screens farther from the aquitard; Erickson and Barnes, 2005b).…”
Section: Regional Settingmentioning
confidence: 98%
“…Concentrations of arsenic in glacial sediments reflect the lithology (bedrock type) over which the major glacial ice lobes flowed (30) and the type of bedrock underlying the current location of glacial sediments.…”
Section: Ch6 Fig1mentioning
confidence: 99%
“…(29) The presence or absence of arsenicbearing metal oxides is related to the source of the sediments, redox conditions in the aquifer, and the original arsenic-bearing minerals. Concentrations of arsenic in glacial sediments reflect the lithology (bedrock type) over which the major glacial ice lobes flowed (30) and the type of bedrock underlying the current location of glacial sediments. (12) For example, in areas where the glacial sediments are derived from arsenic-rich marine shales and redox conditions favor the release of arsenic to groundwater, the groundwater tends to have high arsenic concentrations.…”
Section: Ch6 Fig1mentioning
confidence: 99%
“…3 for location) west of the confluence of the Minnesota and Mississippi Rivers. High arsenic concentrations in the regionally unconfined area of Minnesota may be associated with the overlying Des Moines glacial lobe (Erickson and Barnes, 2005). The extent of the Des Moines glacial lobe shown in figure 33 is from Schumann (1993).…”
Section: Occurrence and Distributionmentioning
confidence: 99%